Changes in step characteristics between the maximum velocity and deceleration phases of the 100 metre sprint run - Bezodis, I. N.; Irwin, G.; Kuntze, G.; Kerwin, D. G. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
In a 100 m sprint race, athletes are unable to maintain their maximum velocity through the finish line. The aim of this study was to investigate the contributions of step length and step frequency to changes in velocity as athletes decelerate. Nine well-trained sprint athletes each performed between three and five maximal 100 m sprints. Velocity, step length and step frequency were measured for individual steps in the maximum velocity (30-40 m) and deceleration (70-80 m) phases. On a group level, velocity and step frequency reduced between the maximum velocity and deceleration phases (p < 0.05), whereas step length did not. Individual athlete analyses revealed that the fastest sprinters tended to maintain velocity in the deceleration phase by combining a significant reduction in step frequency with a significant increase in step length.